A Novel Lentinula edodes Laccase and Its Comparative Enzymology Suggest Guaiacol-Based Laccase Engineering for Bioremediation - Wong, Kin-Sing (Public Library of Science, 2013)
Laccases are versatile biocatalysts for the bioremediation of various xenobiotics, including dyes and polyaromatic hydrocarbons. However, current sources of new enzymes, simple heterologous expression hosts and enzymatic information (such as the appropriateness of common screening substrates on laccase engineering) remain scarce to support efficient engineering of laccase for better “green” applications. To address the issue, this study began with cloning the laccase family of Lentinula edodes. Three laccases perfectio sensu stricto (Lcc4A, Lcc5, and Lcc7) were then expressed from Pichia pastoris, characterized and compared with the previously reported Lcc1A and Lcc1B in terms of kinetics, stability, and degradation of dyes and polyaromatic hydrocarbons. Lcc7 represented a novel laccase, and it exhibited both the highest catalytic efficiency (assayed with 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) [ABTS]) and thermostability. However, its performance on “green” applications surprisingly did not match the activity on the common screening substrates, namely, ABTS and 2,6-dimethoxyphenol. On the other hand, correlation analyses revealed that guaiacol is much better associated with the decolorization of multiple structurally different dyes than are the two common screening substrates. Comparison of the oxidation chemistry of guaiacol and phenolic dyes, such as azo dyes, further showed that they both involve generation of phenoxyl radicals in laccase-catalyzed oxidation. In summary, this study concluded a robust expression platform of L. edodes laccases, novel laccases, and an indicative screening substrate, guaiacol, which are all essential fundamentals for appropriately driving the engineering of laccases towards more efficient “green” applications.